Goal planning Brook visits Christina and Roy - Oregon Commission on Children and Families (Oregon : Oregon Commission on Children and Families, 2002)
Talk about the goal planning in child rearing starting from early childhood
Title from title screen
Reality-based training for home visitor
Executive producer, Fritz Jenkins ; executive director, Donna Middleton
Keywords: Child rearing; Child development; Parenting; Child care